The effects of newly formulated filter aids material loading on pressure drop and particle penetration - Abd. Rahim, Siti Hajar (ATLANTIS PRESS, 2016)
Filter aids have been widely used in air filtration system in order to fulfill the needs to expand the lifespan of the fabric filter as well as to improve the collection efficiency of particles during filtration and separation operations. The efficiencies of PrekotAC that consists of a different combination of power activated carbon and pre-coating material, PreKot(TM) in terms of its pressure drop across a filter media and collection efficiency are highly influenced on the material loading of a material used during filtration process. PrekotAC was formulated into four different weight ratios and tested under a constant air flow rate of 4 L/min and three different material loadings of 0.2, 0.4 and 0.6 mg/mm 2 . It was found that the higher the material loading is the higher the pressure drop across a filter media becomes. The results also showed that the penetration of particles were reduced significantly as material loading increases where higher material loading leads to higher collection efficiencies of particles.